To (or not to) label products as artisanal: effect of fashion involvement on customer perceived value. Issue 2 (18th April 2017) - Bhaduri, Gargi; Stanforth, Nancy
Abstract : Purpose: This paper aims to understand whether product descriptor cues related to artisanal qualities can help marketers to delineate their clothing product offerings to consumers by influencing consumers' perceived product values and the effect (if any) of consumers' fashion clothing involvement on such value perceptions. In today's intensely competitive market environment marked by minimal product differentiation, marketers are often using the terms artisan, handcrafted or similar to indicate that their products are different, produced with care, are of higher quality and even premium. Design/methodology/approach: For the study, a 2 (Involvement: High/Low) × 4 (Cues: Control/Artisan-made/Part of a curated collection/Handcrafted) × 2 (products replications: Jeans/Handbags) mixed model repeated measures experiment was designed. A sample of 487 adult female US consumers was recruited using a market-based research firm. Findings: Results indicated that framing luxury products as artisanal using product descriptor cues influenced the perceived value of these products. Moreover, consumers' fashion involvement positively influenced their perceived value for artisanal luxury products. Originality/value: The study is one of the few attempts in understanding the value of artisanal luxury products. Given the importance of the artisanal luxury industry to the global economy, focusing on how consumers perceive the value of artisanal luxury products is important to marketers and practitioners as well as academicians. From a theoretical perspective, the study indicates fashion involvement as a predictor of consumers' perceived value, thereby filling a gap in literature. The study used two different product categories to aid in generalizability of the results.